Menopause and Depressive Symptoms in the UK Biobank - Hira Mayet; Katie Marwick; Magdalena Pfaff; James M Stone (BJPsych Open)
Aims: The UK Biobank is a large-scale prospective cohort study with data collected on over 500,000 individuals within the United Kingdom. We sought to understand whether the years around the menopause are associated with an increased likelihood of depressive symptoms, using the PHQ-2 questionnaire, which screens for depressive disorders. A score of 3 or above is suggestive of a depressive disorder. Our analysis looked at the likelihood of having significant depressive symptoms in the years before and after the final menstrual period.